Dudnienie kroków. Trewirski wiersz Stefana Napierskiego - Zieliński, Jan (Załącznik Kulturoznawczy, 2021)
An analysis of the poem Zegary w Trewirze (Clocks in Trier) by Stefan Napierski from his 1933 volume Obrazy z podróży (Travel Pictures). The interpretation includes on one hand the context of the only novel by Napierski, Rozmowa z cieniem (Conversation With a Shadow), in which the clocks play an important role, on the other hand the iconographical tradition of the time measuring in Trier, based mostly on the monography of that subject by Christl Lehnert-Leven (Uhren in Trier. Geschichte, Gedichte und Bestände des Museums Simeonstift Trier, 1992). There is also a discussion of the allusions to Heinrich Heine and Rainer Maria Rilke, both in Napierski’s poem and in his novel, as well as a presentation of two Middle Ages legends: about the founding of the town of Trier by the king Trebeta and about the life-story of St. Simeon, a hermit buried alive at the town’s gates, which help to explain the deeper meaning of Napierski’s poem.